Taste for variety and optimum product diversity in an open economy - Javier Coto-Martínez; María D. C. García-Alonso; Paul Levine (University of Kent, Department of Economics, 2005)
We extend the Benassy (1996) 'taste for variety' model to an open economy setting. With the Benassy effect, the market equilibrium is inefficient, openness reduces the varieties provided in the unconstrained optimum and there are potential gains from international coordination.
Keywords: D43; F12; 330; Taste for variety; monopolistic competition; Benassy effect; open economy